The Effect of Angkak Addition Towards DPPH Antioxidant Activity and Yields in Mixed Angkak-Red Ginger Extracts - Christy, Clarissa; Nugraha, Fajar; Fahrurroji, Andhi; Anastasia, Desy Siska (Biology, Medicine, & Natural Product Chemistry, 2025)
Angkak and red ginger, which represents West Borneo’s Chinese ethnic group’s herbal cooking, were studied to produce antioxidant activity through shogaol along with monacolin K and respond to DPPH (2, 2-diphenyl-1-picrylhydrazyl) test. This research aims to combine the two ingredients into extracts and observe how they affect the yields and IC50 value. Methods were started with the extraction of both materials in a variety of simplicia powder weights using 800 rpm stirring speed at 60°C for 120 minutes. The extracts were then tested for percentage yield (%), Thin Layer Chromatography (TLC), and half-maximal inhibitory concentration (IC50) value. IBM SPSS Statistics 25 analysis was also carried out at the end for yields and IC50 values data. Results showed that the angkak addition affected the IC50 value without giving any significant impact on each yield amount (p-value>0,05). Increased angkak in the variations led to the IC50 values decrease, ranging from 122.996 ppm (Mix 1) to 225.399 ppm (Mix 3). Angkak’s pigments and red ginger’s polyphenol compounds which provide antioxidant ability were found to occupy Mix extracts based on the TLC profile. In conclusion, angkak decreased the DPPH antioxidant activity of its extract combination with red ginger, but did not affect the yield percentage.